2013
DOI: 10.5539/ass.v9n15p47
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Innovative Work Behavior in the Knowledge Intensive Business Services Sector in Malaysia

Abstract: Innovative work behavior plays a central role in the long-term survival of knowledge-intensive business services in Malaysia. Even though innovation and creativity and their influences on the Malaysian economy and its future growth are important, research on this area is still inadequate. Underpinned by the Social Exchange Theory, this empirical study attempts to determine the relationship that may exist between pro-innovation climate, leader-member exchange (LMX), and social capital with the innovative work b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 65 publications
(63 reference statements)
1
12
1
Order By: Relevance
“…According to , job autonomy has frequently been identified as one of Innovative Work Behaviour (Klaeijsen et al, 2017;Awang-Hashim et al, 2017;Dhar, 2016;Jaisingh, 2015;) (Bawuro, 2018;A. Ghani et al, 2016;Hakimian et al, 2016;Orindah, 2014;Thien et al, 2014;Fairuz et al, 2013) (Werleman, 2016;Abdullah et al, 2016;Sapie et al, 2015;Kheng, June, et al, 2013;Hsiao et al, 2011; J. De the major antecedents of employee creativity and increases the making of suggestions for improvements in any innovation development.…”
Section: Propose Framework and Conclusionmentioning
confidence: 99%
“…According to , job autonomy has frequently been identified as one of Innovative Work Behaviour (Klaeijsen et al, 2017;Awang-Hashim et al, 2017;Dhar, 2016;Jaisingh, 2015;) (Bawuro, 2018;A. Ghani et al, 2016;Hakimian et al, 2016;Orindah, 2014;Thien et al, 2014;Fairuz et al, 2013) (Werleman, 2016;Abdullah et al, 2016;Sapie et al, 2015;Kheng, June, et al, 2013;Hsiao et al, 2011; J. De the major antecedents of employee creativity and increases the making of suggestions for improvements in any innovation development.…”
Section: Propose Framework and Conclusionmentioning
confidence: 99%
“…Innovation ability plays a crucial role in the success of firms, especially knowledge-intensive firms (Kheng, June, & Mahmood, 2013), by increasing the rate of return and capturing higher benefits from the innovative activities (Atkinson, 2014). Innovation ability plays a crucial role in the success of firms, especially knowledge-intensive firms (Kheng, June, & Mahmood, 2013), by increasing the rate of return and capturing higher benefits from the innovative activities (Atkinson, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some scholars also study the innovation competitiveness of a specific industry from a micro-perspective, such as the manufacturing industry and the high-tech industry. Innovation ability plays a crucial role in the success of firms, especially knowledge-intensive firms (Kheng, June, & Mahmood, 2013), by increasing the rate of return and capturing higher benefits from the innovative activities (Atkinson, 2014). Firm clustering is helpful to attract creative professionals (Florida, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most studies of the relationship between LMX and IWB have confirmed that the former has a positive effect on the latter (Altunoglu & Gurel, 2015;Kheng et al, 2013) and that LMX is an important antecedent of IWB (Xerri, M., 2013, Agarwal, 2014. A high level of LMX quality between employees and supervisors will encourage ijbm.ccsenet.org International Journal of Business and Management Vol.…”
Section: Relationship Between Lmx and Iwbmentioning
confidence: 99%